Physiochemical Studies of Sodium Chloride on Mungbean (Vigna radiata L. Wilczek) and Its Possible Recovery with Spermine and Gibberellic Acid - Srijita Ghosh; Sanglap Mitra; Atreyee Paul (The Scientific World Journal)
The physiological and biochemical responses to increasing NaCl concentrations, along with low concentrations of gibberellic acid or spermine, either alone or in their combination, were studied in mungbean seedlings. In the test seedlings, the root-shoot elongation, biomass production, and the chlorophyll content were significantly decreased with increasing NaCl concentrations. Salt toxicity severely affected activities of different antioxidant enzymes and oxidative stress markers. Activities of antioxidant enzymes, superoxide dismutase (SOD), and catalase (CAT) increased significantly over water control. Similarly, oxidative stress markers such as proline, malondialdehyde (MDA), and hydrogen peroxide (H2O2) contents also increased as a result of progressive increase in salt stress. Combined application of NaCl along with low concentrations of either gibberellic acid (5 µM) or spermine (50 µM) in the test seedlings showed significant alterations, that is, drastic increase in seedling elongation, increased biomass production, increased chlorophyll content, and significant lowering in all the antioxidant enzyme activities as well as oxidative stress marker contents in comparison to salt treated test seedlings, leading to better growth and metabolism. Our study shows that low concentrations of either gibberellic acid or spermine will be able to overcome the toxic effects of NaCl stress in mungbean seedlings.